METODOLOGI QIYAS DALAM ISTINBATHHUKUM ISLAM - Sakirman Sakirman (Program Studi Hukum Keluarga Islam, 2018)
Shariah is the concrete embodiment in the middle of thecommunity. Even so, the Shari'ah as puts the teachings of Islamgrew in a variety of situations, conditions and aspects of spacetime.The ontological reality of Shari'ah is then gave birth to theepistemology of Islamic law (fiqh) which is basically a remotelyand called the scholars with a social fact enclosing them. Thesehistorical facts show that Islamic law (fiqh) justification of theplurality of the formulation of the law due to the role ofepistemology